The analysis of the Met - Martinez, Lorena M.; Florendo Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Metropolitan Theater (Manila); Theaters -- Philippines